Corrections to “Fine-Tuned Segment Anything Model (SAM) for Reservoir Extractions Compared With Popular CNNs: An Experiment for Space-Borne Synthetic-Aperture Radar Images” - Nguyen Hong Quang; Hanna Lee; Eui-Myoung Kim; Gihong Kim (IEEE Access)
Presents corrections to the paper, Corrections to “Fine-Tuned Segment Anything Model (SAM) for Reservoir Extractions Compared With Popular CNNs: An Experiment for Space-Borne Synthetic-Aperture Radar Images”.